The Use of Audio-Visual Media in Improving Students' Reading Comprehension and Sholat Movements in Online Learning - Suharsiwi, Suharsiwi; Fadilah, Nur; Farokhah, Laely (Journal of Education Technology, 2022)
In the Covid-19 pandemic situation, learning that requires practice and habituation patterns such as prayer is experiencing obstacles. Teachers and parents also have problems finding the right learning media so that children's prayer understanding is better. Preliminary study obtained data on the ability of elementary school children in Class I is still far from the Minimum Completeness Criteria (KKM) when online learning is implemented since the child enters school. This research used classroom action research, which aims to describe 1)how to apply prayer audio visual media, and 2) how is the student's understanding of prayer which includes aspects of the ability to recite prayer readings and pray according to the sequence of prayer movements. The research subjects were 18 students of class I, with the researcher as a class teacher and the principal as an expert observer and assessor. Methods of data collection using observation and interview. The instrument consists of media assessment by experts, teacher observation instruments and student abilities. The data analysis used is narrative-qualitative, which describes the findings obtained in the implementation of the action in the form of diagrams and tables. The results of the action after using audio-visual media, students' understanding experienced an increase in prayer readings from 11% which was good to 95% good, and movement ability from 6% to 94%. The conclusion is that the use of audio-visual media in online learning can improve students' understanding of prayer on the ability to read and perform movements in accordance with the guidance of the Prophet SAW.